How Leader-Member Exchange Affects Creative Performance: An Examination From the Perspective of Self-Determination Theory - Xie, Zhiyu; Wu, Na; Yue, Tong; Jie, Jing; Hou, Guanghui; Fu, Anguo (Frontiers in Psychology, 2020)
It has been shown that leadership is a major factor that influences creative performance. Although past studies have found that leader-member exchange (LMX) has direct effects on employee creative performance, there continues to be a lack of research examining how the LMX relationship mediates creative performance. This study used self-determination theory to examine the mediating effects of the LMX relationship on creative performance through attitudinal and emotional processes. Participants were supervisors and subordinates of township enterprises in the Pearl River Delta in China. There were 386 valid supervisor-subordinate dyads. Supervisors were responsible for assessing creative performance and the remaining variables were completed by employees. Results showed that high LMX increased the positive moods of subordinates, improved creative performance, and stimulated intrinsic motivation for improvement. Based on the results, we have proposed academic and practical recommendations such as organizations that want to encourage creativity, could begin by training managers to demonstrate high LMX by strengthening their relationships with employees. We also described study limitations, and suggested directions for future studies.